2021
DOI: 10.3390/genes12111795
|View full text |Cite
|
Sign up to set email alerts
|

Macular Dystrophy with Bilateral Macular Telangiectasia Related to the CYP2U1 Pathogenic Variant Assessed with Multimodal Imaging Including OCT-Angiography

Abstract: Purpose: We report the case of a neurologically asymptomatic young boy presenting with an unusual phenotype of CYP2U1 related macular dystrophy associating bilateral macular telangiectasia (MacTel) and fibrotic choroidal neovascularization (CNV), assessed with complete multimodal imaging including optical coherence tomography angiography (OCT-A). Case presentation: A twelve-year-old boy from a non-consanguineous family complained of bilateral progressive visual loss and photophobia. The best-corrected visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…In a French family included in our cohort, [12] the same CYP2U1 pathogenic mutation was observed leading to an extremely severe disability affecting both lower and upper limbs, starting before the first year of age, and accompanied by intellectual disability. In contrast with the other cases reported, carrier members belonging to a Tunisian family recently reported by El Matri et al [13] did not present any symptoms at neurological examination (age at examination: 12 years of age) but manifested visual deficits, similar to those observed in the Italian patients.…”
Section: Clinicogenetic Aspects Of Hereditary Spastic Paraplegia Type 56contrasting
confidence: 80%
See 4 more Smart Citations
“…In a French family included in our cohort, [12] the same CYP2U1 pathogenic mutation was observed leading to an extremely severe disability affecting both lower and upper limbs, starting before the first year of age, and accompanied by intellectual disability. In contrast with the other cases reported, carrier members belonging to a Tunisian family recently reported by El Matri et al [13] did not present any symptoms at neurological examination (age at examination: 12 years of age) but manifested visual deficits, similar to those observed in the Italian patients.…”
Section: Clinicogenetic Aspects Of Hereditary Spastic Paraplegia Type 56contrasting
confidence: 80%
“…Interestingly, CYP2U1 mutations have also recently been implicated in a neurocutaneous syndrome, [15] and it has also been suggested that they could affect the retina, leading to macular dystrophy. [13,[15][16][17] As often observed in HSPs, a huge intra-and inter-familial variability characterize the severity of symptoms presented by SPG56-HSP patients, even among those sharing the same causative mutation. A clear example of this phenomenon is provided by three families sharing a stop mutation (p.Arg390X) leading to the premature termination of CYP2U1 translation.…”
Section: Clinicogenetic Aspects Of Hereditary Spastic Paraplegia Type 56mentioning
confidence: 97%
See 3 more Smart Citations